OPTIMALISASI DESAIN KENDALI KECEPATAN PUTAR MOTOR INDUKSI TIGA FASA BERBASIS FPGA - Tole Sutikno (Universitas Ahmad Dahlan, 2008)
FPGA based the problem of implementation of PWM signal generating system is solution of transformation to digital gate logic space. These stages are done with sampling, quantizing and coding. Best resolution of sampling and carrier frequency, so result of PWM generating is better, but it required most digital gate. Aim of this research is optimization of last research adjustable speed drive of three-phase induction motor; with improve resolution of sampling and carrier frequency, and minimalization of digital gate used with Quine Mc Cluskey method. Result of this research indicate that the design of optimalized SPWM generating signal can be realized in hardwared-logic in ACEXIK FPGA to drive inverter as speed controller turn around the three phase induction motor, with requiring 1629 logic cell. Adjustable motor speed designed can be done by through setting make a modulation index and frequency. At this research, system have been tested at setting frequency 3-50 Hz with the variation of modulation index, and can adjustable three phase induction motor speed in range 117-1468 rpm.